Gonadotropin-releasing hormone agonist triggering is effective, even at a low dose, for final oocyte maturation in ART cycles: Case series - Gülekli, Bülent (J Turk Ger Gynecol Assoc, 2015)
OBJECTIVE: To investigate the efficacy of low-dose gonadotropin-releasing hormone (GnRH) agonist for final oocyte maturation in females undergoing assisted reproductive treatment (ART) cycles. MATERIAL AND METHODS: Nine females undergoing ovarian stimulation in a GnRH antagonist protocol who received triptorelin 0.1 mg to trigger final oocyte maturation were included. Treatment outcomes of these patients were compared with those of controls, matched for age and oocyte number (n=14), who received 0.2 mg triptorelin at the same time. The luteal phase was supported with vaginal micronized progesterone and oral estradiol hemihydrate 2 mg twice daily. RESULTS: The mean (±) numbers of retrieved, metaphase II, and fertilized oocytes were 15.66±7.82, 14±7.28, and 10.11±5.86, respectively. The implantation and clinical pregnancy rates were 46.1% and 71.4%, respectively. Of the pregnancies, 2 were live births, 1 was a preterm birth (twins), 2 are on-going, and 2 ended as miscarriages. No case of OHSS was encountered. On comparison of the results of these patients (fresh cycles; n=7) with those of matched controls, there were no significant differences in terms of retrieved mature oocytes, implantation rates, or clinical pregnancy rates (p>0.05). CONCLUSION: These findings suggest that low-dose GnRH agonist triggering has similar efficacy as standard doses in terms of retrieved mature oocytes and clinical pregnancy rates in in vitro fertilization cycles.